REFLECTIVE practices of educators in a masters' program in Egypt: a case study - Elsayed, Mayada Samy (AUC Knowledge Fountain, 2019)
This paper aims at exploring reflective practices in a Masters’ Program in a private university in Egypt through graduate students’ perspectives of reflective practices. The research examines the graduates’ perception of reflective practices as a tool for enhancement of their learning. Moreover, the study explores how the enrolled graduate students approach reflective practices in terms of comprehension, language, and expression. A mixed methodology is followed where a ten-minute Likert type survey is administered to graduate students in a private Education Masters’ Program in Egypt in the quantitative phase. In the qualitative phase, the participants were voluntarily interviewed to share their personal experiences regarding learning through a reflective process. The findings show the usage of the reflective practices within the program as a tool of learning for the students and a tool for assessing and updating the course material. Moreover, the results reveal that reflective practice is a subjective form of learning; therefore, there should be a language (agreed code of understanding) between the professors and the students that they agree on so that they can assess how far they are grasping the content of the course. Additionally, the findings highlight the significance of the instructor’s guidance in a reflective practice whether through rubrics or through the assignments’ description and instructions. The paper presents some practical implications and recommendations for future research. Keywords: reflective practice, educators, graduate school, mixed-method study